Intellectual Property Rights in Pakistan: Compatibility and Conflict with Shariah Perspectives (Al-Qamar, 2025)
Intellectual property rights in Pakistan are primarily safeguarded through modern legislative frameworks; however, these laws are largely influenced by Western legal traditions. Being an Islamic republic, Pakistan is constitutionally bound under Article 227 to ensure that all enacted laws remain consistent with the teachings of the Qur’an and Sunnah. This raises a critical question regarding the extent to which Pakistan’s intellectual property (IP) legislation aligns with Islamic legal principles. Issues concerning patents, copyrights, and trademarks often intersect with Islamic perspectives on ownership, public utility, and monopoly, thereby creating areas of potential conflict. Furthermore, the compatibility of international agreements—particularly the Trade-Related Aspects of Intellectual Property Rights (TRIPS)—with Islamic values remains ambiguous. This study explores the concept of intellectual property within the framework of Islamic jurisprudence and its correlation with broader legal and ethical provisions of Shariah. It emphasizes that Islam recognizes both tangible and intangible property rights and provides mechanisms for their protection. The research also examines the primary sources of Islamic law—the Qur’an, Sunnah, Ijma, and Qiyas—as foundations for rights, responsibilities, and the safeguarding of human effort. Additionally, it highlights the objectives of Maqasid al-Shariah, which aim to preserve religion, life, intellect, lineage, and wealth, thereby offering a holistic framework to assess the alignment of intellectual property laws with Islamic principles.
Keywords: Islamic law, Copyright law, Patent, Trademark, TRIPS agreement, Constitution of Pakistan